Effects of calcination on the crystallography and nonbiogenic aragonite formation of ark clam shell under ambient condition - Loy, Chee Wah; Matori, Khamirul Amin; Lim, Way Foong; Schmid, Siegbert; Zainuddin, Norhazlin; Abdul Wahab, Zaidan; Alassan, Zarifah Nadakkavil; Mohd Zaid, Mohd Hafiz (Hindawi Publishing Corporation, 2016)
This paper presents a study of crystallographic evolution of disposed ark clam shell (ACS) after calcination at 400–1400°C which was kept at room temperature under ambient condition in Malaysia during nine months. A better understanding of hydration and recarbonation of ACS powder (≤63 μm) after calcination was discovered by PXRD and FTIR. The research focuses on the crystallographic transformation, biogenic calcite decomposition, and unusual atmospheric aragonite formation in ACS after calcination and atmospheric air exposure. Ex situ PXRD showed calcite present in ACS at ≤900°C. ACS transformed to pyrogenic fcc CaO at ≥800°C after three months. Long term atmospheric air exposure of decarbonized ACS caused nucleation of nonbiogenic aragonite, vaterite, calcite, and portlandite. However, in situ PXRD analysis of ACS at instantaneous temperature without cooling process does not indicate the presence of aragonite, vaterite, and portlandite crystals. FTIR spectra revealed CaO–CO2 bond in ACS dissociated with temperature (600–900°C) to form CaO and CO2. Ca–OH bond was also traced in FTIR spectra of ≥700°C. It resulted by hydroadsorption of CaO with H2O in atmospheric air.